Empowerment of nurses in qatar: unveiling the relationship between self-esteem, psychological empowerment, and assertiveness - George V. Joy; Atul Deshmukh; Kalpana Singh; Abdulqadir J. Nashwan; Badriya Al-Lenjawi (BMC Nursing)
Abstract Background Nurses are vital to healthcare systems, yet their psychological well-being remains underexplored despite its critical impact on professional performance and job satisfaction. Essential attributes such as self-esteem, psychological empowerment, and assertiveness play a crucial role in effective decision-making and advocacy. In Qatar, the National Health Strategy (2024–2030) emphasizes healthcare worker empowerment; however, research on the interplay of these psychological constructs among nurses is scarce. Aim This study aims to evaluate the levels of self-esteem, psychological empowerment, and assertiveness among nurses in Qatar and examine their interrelationships, particularly the mediating role of self-esteem between empowerment and assertiveness. Methodology A quasi-experimental one-group pre-posttest design was employed, focusing on baseline data from 144 registered nurses across Hamad Medical Corporation (HMC) facilities. Data were collected using validated tools, including the Rosenberg Self-Esteem Scale, Psychological Empowerment Scale, and the Rathus Assertiveness Schedule. Statistical analyses, including structural equation modeling and ANOVA, were conducted to identify relationships and demographic associations. Results Findings indicated moderate levels of assertiveness (mean = 67.1 ± 10.9) and empowerment (mean = 51.1 ± 5.9), along with high self-esteem (mean = 27.1 ± 2.9). Empowerment significantly influenced assertiveness (β = 0.207, p = 0.009); however, self-esteem did not mediate this relationship. Significant demographic variations in self-esteem were observed, with higher levels reported among early-career nurses and general registered nurses, while assertiveness and empowerment remained consistent across demographic groups. Conclusion The study underscores the importance of fostering empowerment, self-esteem, and assertiveness among nurses through targeted interventions such as assertiveness training and supportive organizational policies. Future research should explore longitudinal changes in these psychological dynamics to enhance sustained professional development. Clinical trial number Not applicable.